Pemanfaatan Microsoft Excel sebagai Inovasi Pencatatan Keuangan untuk Meningkatkan Efektivitas UMKM Toko Rizaki Konveksi Mahasiswa Medan - ButarButar, Yoseph; Fatimah Azzahra; Elsadai Stela Br Sitepu (Prodi Pendidikan Administrasi Perkantoran UNIMED, 2024)
This study aims to determine the effect of using Microsoft Excel in financial recording on the effectiveness of the MSME Toko Rizaki Konveksi Mahasiswa Medan. This research employed a quantitative approach with an associative method. Data were collected through questionnaires distributed to 13 respondents consisting of the owner and employees. Data analysis was performed using simple linear regression through SPSS. The results showed that the use of Microsoft Excel had a positive and significant effect on MSME effectiveness with an R Square value of 0.610 and a significance level of 0.002. This indicates that using Microsoft Excel improves efficiency, accuracy in recording, and better decision-making. These findings demonstrate that digital financial recording using Excel enhances MSME effectiveness and competitiveness in the modern era.